Tranexamic Acid for Acute Spontaneous Intracerebral Hemorrhage: A Meta-Analysis of Randomized Controlled Trials - Guo, Yu; Guo, Xin-Mei; Li, Rui-Li; Zhao, Kai; Bao, Qiang-Ji; Yang, Jin-Cai; Zhang, Qiang; Yang, Ming-Fei (Frontiers in Neurology, 2021)
Background: The role of tranexamic acid (TXA) in preventing hematoma expansion (HE) in patients with acute spontaneous intracerebral hemorrhage (ICH) remains unclear. We aim to investigate the efficacy and safety of TXA in acute spontaneous ICH with a particular focus on subgroups. Methods: Randomized controlled trials (RCTs) were retrieved from CENTRAL, Clinicaltrials.gov, EMBASE, PubMed, and WHO ICTRP. The primary outcome measurement was HE. The secondary outcome measurements included 3-month poor functional outcome (PFO), 3-month mortality, and major thromboembolic events (MTE). We conducted subgroup analysis according to the CT markers of HE (standard-risk population and high-risk population) and the time from onset to randomization (> 4.5h and ≤ 4.5h). Results: We identified 7 studies (representing 5 RCTs) involving 2650 participants. Compared with placebo, TXA may reduce HE on subsequent imaging (odd ratio [OR] 0.825; 95% confidence interval [CI] 0.692-0.984; p-value = 0.033; I2 = 0 %; GRADE: moderate certainty). TXA and placebo arms did not differ in the rates of 3-month PFO, 3-month mortality, and MTE. Subgroup analysis indicated that TXA reduced the risk of HE in the high-risk population with CT markers of HE (OR 0.646; 95% CI 0.503-0.829; p-value = 0.001; I2 = 0 %) and in patients who were treated within 4.5 h of symptom onset (OR 0.823; 95% CI 0.690-0.980; p-value = 0.029; I2 = 0 %), but this protective effect was not observed in the standard-risk population and patients who were treated over 4.5 h of symptom onset. Conclusions: TXA may decrease the risk of HE in patients with acute spontaneous ICH. Importantly, the decreased risk was observed in patients who were treatable within 4.5 h and with a high risk of HE, but not in those who were treatable over 4.5 h and standard-risk population. However, PFO or mortality at 3 months did not differ significantly between patients who received TXA and those who received placebo. TXA is safe for acute spontaneous ICH without increasing MTE.